Physical oceanography during GOAL cruise ESTARTE (2014) - Rodrigo Kerr; Iole Beatriz Marques Orselli (PANGAEA, 2025)
This dataset contains temperature, salinity, dissolved oxygen, and fluorescence profiles collected in the shelf-break region of the South Brazil Bight (SBB) and Southern Brazilian Shelf (SBS) between 23 to 33 of south latitude in October 2014. These measurements were made during the EstARte cruise carried out by the Brazilian Ocean Acidification Network (BrOA) and High Latitude Oceanography Group (GOAL_FURG) onboard the NHOc Cruzeiro do Sul. The EstARte project aims to obtain physical and biogeochemical processes controlling carbon exchanges at the air-sea interface and ocean acidification in the South Atlantic continental shelf and slope. Salinity and temperature were measured using CTD (conductivity, temperature, and depth), and fluorescence and dissolved oxygen were obtained using auxiliary sensors installed in the CTD.